Effects of organic additives on calcium hydroxide crystallisation during lime slaking. (January 2021) - Pesce, Cecilia; Pesce, Giovanni Luca; Molinari, Marco; Richardson, Alan
Abstract: Organic compounds, often used in cement systems as admixtures, may affect the crystallisation and carbonation kinetics of Ca(OH)2, an important phase of hydrated cement. Here, we investigated changes in Ca(OH)2 morphology in the presence of 3 organic compounds, commonly encountered in cement and lime-based materials: sucrose, pectin and calcium lignosulfonate. The additives were introduced either before or after lime slaking to determine the influence of temperature. Ca(OH)2 crystals and supernatant solutions were characterised at time of slaking and after 6 months of ageing using scanning electron microscopy, X-ray diffraction and optical emission spectroscopy. Our results indicate that the morphology of Ca(OH)2 crystals is modified by the characteristics of the organic molecules which promote formation of Ca(OH)2 with habits that can result in faster carbonation, an effect that is detrimental to cement used in reinforced concrete. These effects are enhanced when the additives are introduced before slaking, likely as a result of thermal degradation. Highlights: Sucrose and lignosulfonate reduce the crystallite size of Ca(OH)2 . Lime slaking in sucrose solutions leads to Ca(OH)2 with irregular shape. Lime slaking in presence of lignosulfonate leads to plate-like Ca(OH)2 crystals. Effects of additives are enhanced when introduced before slaking. Additives stabilise the unstable edge faces of Ca(OH)2 during ageing.